THE CRIMINALIZATION OF INTENTIONAL BANKRUPTCY: A COMPARATIVE STUDY - Akbarkhon Azamov (Western European Studies, 2025)
This study examines the legal frameworks governing intentional bankruptcy across different jurisdictions, analyzing the rationale, enforcement mechanisms, and penalties associated with fraudulent insolvency. The paper explores how various legal systems define and penalize bankruptcy fraud and the implications of criminalizing such financial misconduct.
Keywords: Bankruptcy fraud; Insolvency law; Fraudulent bankruptcy; Financial misconduct